2021
DOI: 10.1111/jns.12465
|View full text |Cite
|
Sign up to set email alerts
|

Report of a fulminant anti‐pan‐neurofascin‐associated neuropathy responsive to rituximab and bortezomib

Abstract: Inflammatory neuropathies with pathogenic involvement of the nodes of Ranvier through autoantibodies have been increasingly characterized in the past years.The so-called anti-pan-NF-associated neuropathies caused by the simultaneous existence of anti-Neurofascin-186/-140 and -155-antibodies are extremely rare and cause life-threatening symptoms. Therapeutic strategies are needed as symptoms may be life-threatening and may not respond to standard first-line CIDP treatment. We report a case of a 52-year-old male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
0
14
1
Order By: Relevance
“…Among IgG4-AID, bortezomib was described as a good therapeutic option for CIDP patients ( 228 ) with severe relapses or an acute progression who did not respond adequately to regular immunosuppression treatment and rituximab ( 228 ). Additionally, in a patient with anti-pan-NF-associated neuropathy (predominantly of the IgG4 isotype) with severe clinical manifestations, it has also being shown reduction in antibody titer leading to clinical improvement after receiving a combination of IVIG, PLEX, rituximab and bortezomib ( 229 ). Bortezomib was beneficial in patients with relapsed/refractory TTP with an acceptable adverse event profile ( 230 ).…”
Section: Treatments Of Igg4 Neurological Diseasesmentioning
confidence: 99%
“…Among IgG4-AID, bortezomib was described as a good therapeutic option for CIDP patients ( 228 ) with severe relapses or an acute progression who did not respond adequately to regular immunosuppression treatment and rituximab ( 228 ). Additionally, in a patient with anti-pan-NF-associated neuropathy (predominantly of the IgG4 isotype) with severe clinical manifestations, it has also being shown reduction in antibody titer leading to clinical improvement after receiving a combination of IVIG, PLEX, rituximab and bortezomib ( 229 ). Bortezomib was beneficial in patients with relapsed/refractory TTP with an acceptable adverse event profile ( 230 ).…”
Section: Treatments Of Igg4 Neurological Diseasesmentioning
confidence: 99%
“…The others received rituximab, in one case in combination with bortezomib. 27 They showed major motor improvement (ΔMRC 43/48/58) and sNF-L levels < 70 ng/ml in follow-up intervals of 4–11 months, with one of them reaching sNF-L levels within the normal range of healthy controls (3 standard deviations) 9 months after the onset of disease. Supplementary Video 1 shows one of them happily leaving the rehabilitation clinic.…”
Section: Resultsmentioning
confidence: 92%
“… 12 , 20–27 A distinct clinical phenotype has been proposed in this subset: they present with a severe, GBS-like onset and after initial short recovery, develop a fulminant course of disease with tetraplegia, autonomic instability, cranial nerve involvement, respiratory failure with prolonged ventilation, insufficient response to standard treatment and a high mortality. 12 , 20 , 21 , 26 , 27 …”
Section: Introductionmentioning
confidence: 99%
“…The so-called anti-pan-NF-associated neuropathies caused by the co-existence of anti-NF186/140 and NF155 antibodies were extremely rare and caused life-threatening symptoms such as almost locked-in syndromes [ 9 , 11 , 12 , 19 , 20 , 28 ]. Burnor et al [ 10 ] reported a 50-year-old man who developed rapidly progressive weakness and paresthesias, which evolved into extraocular weakness, ptosis, facial diplegia, dysarthria, almost complete ophthalmoplegia, quadriplegia, and oscillating sympathetic hypersensitivity with labile blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the symptoms were quite mild and revealed an effective clinical response to IVIG, so no further immunotherapy was required. Fels et al [ 28 ] described a case of fulminant anti-pan-NF-associated neuropathy as IgG4 and IgG3-mediated disease with severe clinical damage. The patient presented with progressive tetraplegia, sensory impairment, cranial nerve involvement, autonomic dysregulation and respiratory insufficiency.…”
Section: Discussionmentioning
confidence: 99%